Blockchain Technology: Revolutionizing Data Security in Energy Trading Risk Management - Niranjan Mithun Prasad (International Journal of Scientific Research in Computer Science, Engineering and Information Technology, 2025)
This comprehensive article explores the transformative impact of blockchain technology on energy trading risk management systems. The article examines how blockchain addresses critical challenges in data security, transparency, and regulatory compliance within the energy sector. Through detailed analysis of distributed ledger infrastructure, smart contract integration, and cryptographic security measures, the research demonstrates significant improvements in operational efficiency, transaction processing, and risk mitigation. The investigation encompasses automated compliance frameworks, data privacy mechanisms, and scalability solutions, highlighting how blockchain technology enhances market participation while reducing operational costs. The article also evaluates emerging technologies and industry standards, providing insights into future developments that will shape secure and efficient energy trading operations.